2017
DOI: 10.1038/srep45840
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Biogeography and Core Microbiota of the Rat Digestive Tract

Abstract: As a long-standing biomedical model, rats have been frequently used in studies exploring the correlations between gastrointestinal (GI) bacterial biota and diseases. In the present study, luminal and mucosal samples taken along the longitudinal axis of the rat digestive tract were subjected to 16S rRNA gene sequencing-based analysis to determine the baseline microbial composition. Results showed that the community diversity increased from the upper to lower GI segments and that the stratification of microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
132
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(156 citation statements)
references
References 94 publications
23
132
1
Order By: Relevance
“…Analysis of bacterial composition by 16S rRNA sequencing showed that HFD treatment reduced α‐diversity of gut microbiome (Figure C), which was normalized when high‐fat feeding was enriched with bilberry ( p < 0.01). The rat microbiota was found dominated by the phyla Firmicutes and Bacteroidetes , consistent with previous descriptions . HFD profoundly increased the Firmicutes / Bacteroidetes ratio in fecal samples (Figure D, p < 0.001), whereas HFD+BB normalized this ratio to the level of LFD and LFD+BB group ( p < 0.001).…”
Section: Resultssupporting
confidence: 89%
“…Analysis of bacterial composition by 16S rRNA sequencing showed that HFD treatment reduced α‐diversity of gut microbiome (Figure C), which was normalized when high‐fat feeding was enriched with bilberry ( p < 0.01). The rat microbiota was found dominated by the phyla Firmicutes and Bacteroidetes , consistent with previous descriptions . HFD profoundly increased the Firmicutes / Bacteroidetes ratio in fecal samples (Figure D, p < 0.001), whereas HFD+BB normalized this ratio to the level of LFD and LFD+BB group ( p < 0.001).…”
Section: Resultssupporting
confidence: 89%
“…Interestingly, Actinobacteria (subclass: Rothia , Micrococcaceae , Corynebacterium , Corynebacteriaceae , and Actinomyocytes ) and Bacteroidetes (subclass: Bacteroidales ), common phyla associated with a “healthy gut” (Clarke et al, ), were also significantly abundant in the cecal contents of HFD‐fed rats. This is consistent with research that has shown the abundance of Actinobacteria and Bacteroidetes are high in the large intestine of rats (Li et al, ). Moreover, rats in the current study were fed a 60% HFD that contained 6.5% of a dietary fiber called Solka Floc (FCC200).…”
Section: Discussionsupporting
confidence: 93%
“…Due to the strong correlative relationship between the QTL, we tested whether there was a direct interaction between bile acids and Turicibacter . Turicibacter inhabits the small intestine where BAs are secreted upon consumption of a meal (73,74). We screened the human isolate Turicibacter sanguinis for deconjugation and transformation activity in vitro by HPLC/MS-MS. We found that T. sanguinis deconjugated ∼96-100% of taurocholic acid and glycochenodeoxycholic acid (Fig 5A) within 24 hours.…”
Section: Resultsmentioning
confidence: 99%